Technology of obtaining building ceramics with the use of large-tonnage waste of fuel and energy industry - Shchukina, L.; Fedorenko, E.; Galushka, Ya.; Lihezin, S. (Baltija Publishing, Latvia, 2021)
The monograph considers the peculiarities of the use of multitonnage industrial wastes in the form of ash obtained from thermal power plants and coal preparation and mining wastes in the technology of construction ceramics for various purposes. The data on volumes of waste formation, their composition, properties, functional role in compositions of ceramic masses, peculiarities of application in technological process are given. The monograph is intended for scientists, practical specialists, post-graduate students, and students in the field of ceramic materials science.
Keywords: monograph; industrial waste management; construction ceramics; coal waste; thermal treatment